2020
DOI: 10.1002/elan.202060389
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Paracetamol, Ascorbic Acid, and Caffeine Using a Bismuth–Silver Nanosensor

Abstract: The bimetallic nanoparticles of bismuth-silver were used to modify a disk GCE for the simultaneous electrochemical analysis of caffeine (CAF), ascorbic acid (AA), and paracetamol (PAR). The constructed Bi-AgNPs/GCE illustrated strong electrocatalytic activity towards the oxidation of CAF, PAR, and AA. Under the optimum conditions, the sensor provided linearity for PAR, AA, CAF between 2 to 20 μΜ, 10 to 70 μM, and 2 to 40 μM (n = 3), respectively. The detection limits for CAF, PAR, and AA was 2.36 μM, 0.155 μM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Horst et al [ 62 ] used nanoparticles of bismuth and silver to prepare modified GCE (BiAgNPs/GCE) for the individual and simultaneous determination of caffeine, ascorbic acid, and paracetamol in phosphate buffer solution. The sensing performance of BiAgNPs/GCE was also validated in real pharmaceutical formulations for target analytes using differential pulse voltammetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horst et al [ 62 ] used nanoparticles of bismuth and silver to prepare modified GCE (BiAgNPs/GCE) for the individual and simultaneous determination of caffeine, ascorbic acid, and paracetamol in phosphate buffer solution. The sensing performance of BiAgNPs/GCE was also validated in real pharmaceutical formulations for target analytes using differential pulse voltammetry.…”
Section: Discussionmentioning
confidence: 99%
“…Geto and Brett [ 55 ], Guan et al [ 68 ], Jose et al [ 57 ], and Monteiro et al [ 93 ] noticed a linear relationship between the peak current (I p ) and the square root of the scan rate (v 1/2 ), indicating a diffusion-controlled process. On the other hand, Horst et al [ 62 ] and Varsha et al [ 21 ] observed a linear relationship between the peak current (I p ) and the scan rate (v), suggesting that the process is adsorption-controlled. In the paper by Kumar et al [ 58 ], the oxidation mechanism of caffeine on Co 3 O 4 NS-modified GCE in an acetate buffer solution was described as a process controlled by diffusion and adsorption, while Santhosh et al [ 76 ] indicated that it is only an electrolytic redox process and a quasi-reversible electron transfer between caffeine and the CMCPE electrode’s surface.…”
Section: Discussionmentioning
confidence: 99%